2008
DOI: 10.1186/1471-2474-9-20
|View full text |Cite
|
Sign up to set email alerts
|

A role for subchondral bone changes in the process of osteoarthritis; a micro-CT study of two canine models

Abstract: Background: This study evaluates changes in peri-articular bone in two canine models for osteoarthritis: the groove model and the anterior cruciate ligament transection (ACLT) model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
99
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 39 publications
18
99
2
1
Order By: Relevance
“…The early reduction in plate thickness is in concurrence with a previously published pilot study that demonstrated that subchondral plate thinning at 3 and 10 weeks of OA development even may precede cartilage damage. (13) Also, others have demonstrated that plate thinning is an early feature in the OA process. (15,36) Unfortunately, in our study group, size and variation in bone and cartilage parameters were too small to perform meaningful correlations between values of plate thickness and cartilage degeneration for each group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The early reduction in plate thickness is in concurrence with a previously published pilot study that demonstrated that subchondral plate thinning at 3 and 10 weeks of OA development even may precede cartilage damage. (13) Also, others have demonstrated that plate thinning is an early feature in the OA process. (15,36) Unfortunately, in our study group, size and variation in bone and cartilage parameters were too small to perform meaningful correlations between values of plate thickness and cartilage degeneration for each group.…”
Section: Discussionmentioning
confidence: 99%
“…Do these early changes normalize over time, or are they the necessary trigger resulting in subchondral sclerosis? Although a short longitudinal pilot study has been performed, (13) it is clear that longer follow-up studies for both models are needed. Do latestage plate thickening and increase in trabecular volume also develop in the groove model, or is it a consequence of the early decrease in trabecular volume parameters seen only in the ACLT model?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Jacobsen et al (2007) showed that the reduction of intra-articular space in the hip was correlated with the decrease in mineral density of sub-chondral bone in postmenopausal women. It was suggested that the alteration of bone structure can cause changes in the load distribution within the joint and promote the development of OA (Sniekers et al 2008). In this case, the favorable effect of estrogen on cartilage may be due in part to the anti-resorption effect of 17-E2 on bone.…”
Section: Sub-chondral Bone Regulationmentioning
confidence: 99%